Quality of reporting in sports injury prevention abstracts according to the CONSORT and STROBE criteria: an analysis of the World Congress of Sports Injury Prevention in 2005 and 2008. Issue 3 (26th July 2009) - Yoon, Uzung; Knobloch, Karsten
Abstract : Objective: The quality of reporting in congress abstracts is likely to influence clinical decision-making. Hypothesis: The quality of reporting in sports injury prevention abstracts has increased over the last 3 years, as did the number of randomised controlled trials (RCT). Methods: 154 abstracts from the 2005 and 186 abstracts from 2008 World Conferences on Sports Injury Prevention in Norway were analysed. Main outcome measures: Scores of 17 Consolidated Standards of Reporting Trials (CONSORT) criteria for RCT, or 22 Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) criteria for observational studies were determined. Results: Improvement in reporting was evident in RCT (CONSORT score 5.8±0.9 vs 8.6±2.9, p=0.001, CI −4.29 to −1.43) as well as for observational studies (STROBE score 7.9±1.6 vs 9.9±1.7, p<0.001, CI −2.34 to −1.53) between 2005 and 2008. RCTs were published in 9.1% in 2005 versus 10.2% in 2008 (p=0.727). RCT demonstrated a significant improvement in main outcome (0% vs 57.9%, p<0.001). For observational studies, a significant improvement was reported in rationale (53.5% vs 98.2%, p<0.001), objectives (82.2% vs 95.1%, p=0.012), study design (25.2% vs 65%, p<0.001), setting (43.7% vs 65.6%, p=0.002), variables (20.7% vs 74.2%, p<0.001), participants (0.7% vs 10.4%, p=0.001) and funding (0% vs 5.5%, p=0.006). Conclusion: While the percentage of published RCTs in abstracts at the World Congress of Sports Injury Prevention remained unchanged, an improvement in reporting of abstracts was evident from 2005 to 2008, as determined by CONSORT/STROBE criteria. However, substantial and comprehensive use of the CONSORT and STROBE criteria might further increase the quality of reporting of sports injury conference abstracts in the future.